Current trends in antimicrobial use and the role of antimicrobial stewardship in palliative oncology: a narrative review - Bassem Awada; Aref Zribi; Ahmad Al Ghoche; Souha S. Kanj (BMC Palliative Care)
Abstract Background The overuse of antimicrobials is prevalent in palliative oncology care, with up to 86.9% of terminal cancer patients receiving these agents during end-of-life care. This overutilization stems from recurrent infections due to immunosuppression, malnutrition, and frequent hospitalizations, as well as difficulty differentiating infection-related symptoms from cancer-related complications. Discussion Antimicrobial use in palliative cancer care offers limited symptomatic relief while posing significant risks, including Clostridioides difficile infections, multidrug resistance, and patient dissatisfaction. The lack of clear survival benefit highlights the need for judicious antimicrobial use, particularly in terminally ill patients. Effective antimicrobial stewardship strategies, such as integrating infection management into goals-of-care discussions, early referrals to specialized palliative care teams, and implementing early intravenous-to-oral antimicrobial switches, are critical for balancing patient comfort and minimizing unnecessary antibiotic exposure. Conclusion Optimizing antimicrobial use in palliative oncology care requires a multidisciplinary approach that prioritizes patient-centered goals, minimizes harm, and addresses misconceptions about antibiotic efficacy in end-of-life care. Antimicrobial stewardship programs, when tailored to palliative settings, play a vital role in reducing overuse and improving care quality in this vulnerable patient population. Graphical Abstract